Design of dual transmitter and single receiver coil to improve misalignment performance in inductive wireless power transfer system for electric vehicle charging applications - S. Kodeeswaran; S. Julius Fusic; A. Kannabhiran; M. Nandhini Gayathri; Sanjeevikumar Padmanaban (Results in Engineering)
As electric vehicles (EVs) become more prevalent, ensuring efficient wireless charging despite vehicle misalignment is a critical challenge. This research work proposes a two-transmitter coil to reduce misalignment and improve the performance of the static inductive wireless power transfer (IWPT) system. The two transmitter coils are taken in the same dimensions, the inner terminals and outer terminals of the coils are interconnected. The current is applied to the transmitters, producing a magnetic field to transfer the power from the transmitter to the receiver. The finite element analysis carried out in the ANSYS Maxwell simulation is used to calculate the mutual and self-inductance of the proposed IWPT system. The high frequency (HF) converter produces high-frequency AC to transfer the power from the source side to the load side. The double-sided LCC compensation circuits are used on the transmitter and receiver sides to reduce the reactive power component present in the transmitted power. The rectifier on the receiver side converts AC to DC to charge the battery. To reduce misalignment and improve the efficiency of the IWPT, the proposed interconnected two transmitter terminals idea is performed well when there is a change in the position of the vehicle. The LTspice simulation and experimental result shows that the proposed system achieves 1.95 kW with an efficiency of 93.07% at an air gap of 150 mm.